Hr Development Strategy In The Industrial 4.0 Revolution In The Pandemic Of Covid-19 - Endah Fantini; Nidaul Izzah; Elfa Setiawan; Dedy Kusna Utama; Samsudin (Ilomata International Journal of Management, 2021)
The era of the industrial revolution 4.0 is an absolute and unavoidable phenomenon in the business world. The survival of a company depends on the strategy devised to be able to carry out transformation and innovation to deal with it. So that companies and businesses that have been built are not crushed by the times and are hampered by their development, the company must be responsive to existing changes, especially with the development of technology and digital business. The company must also have an integrated travel map so that the direction of business development is clearly visible. The Covid-19 pandemic has changed many things of life in an instant. Never before in modern human history has a pandemic progressed and spread rapidly like Covid-19. Therefore, every event, response, and reaction is also oftentimes good. It happens at the individual level, the smallest community, up to the State and nation. Organizations and corporations are also forced to adapt quickly to very high levels of uncertainty. With the incessant change of life lines into all-digital. Therefore, companies really need to prepare reliable human resources and technology literacy in order to continue to achieve success. Employees should be supported and encouraged to continue learning and increase their knowledge of technology. Because the workforce or human resources who are able to apply and control technology in the present are able to move forward. This study aims to analyze the effect of human resource competence and the use of information technology in the Industrial Revolution Era 4.0 during the co-19 pandemic. In this study using the theory of Computer Mediated Communication (CMC) to examine more in how the process of forming HR groups in the advertising agenda through digital media and also the process of interaction developed by the HR groups. The method in this study uses a qualitative research method with a Case Study approach and the paradigm used is the constructivist paradigm, which is to examine how the interaction and role of HR in the interaction and communication groups in the online media. In this study trying to identify the personalities of each grouped as tourists, mingles, and devotes. Data collection is done by using observation and also conducting in-depth interviews. In addition, the data analysis technique used is to use a flow model from Miles and Huberman consisting of 3 stages, namely Data Reduction, then the presentation of data, and drawing conclusions.